EFFECT OF CHOLINERGIC STIMULATION OF THE AMYGDALOID COMPLEX ON WATER AND SALT INTAKE - Saad, W. A.; Bengtson, R. M.; Menani, José Vanderlei [UNESP]; Camargo, LAA; Renzi, Antonio [UNESP]; Silveira, JEN (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
The effect of carbachol (80 nmol/mul) injection into the amygdaloid nuclear complex (AMG) on sodium appetite and water intake was studied in male Holtzman rats weighing 240-270 g. Twenty-five satiated rats and 38 water-deprived rats were used in the experiment on water intake. In the experiment on sodium intake, 19 rats were injected with atropine + carbachol and 9 rats with hexamethonium + carbachol. After carbachol injection into the AMG, water intake decreased in rats submitted to 30 h of water deprivation (10.28 +/- 1.04 ml/120 min vs 0.69 +/- 0.22 ml/120 min). The decrease in water intake was blocked by prior local injection of a tropine (20 nmol/1 mul)(11.66 +/- 1.46 ml/120 min vs 0.69 +/- 0.22 ml/120 min), but not of hexamethonium (30 nmol/1 mul), into the AMG. In water-deprived animals, carbachol injection into the AMG caused a decrease in sodium chloride intake (6.16 +/- 1.82 ml/h vs 0.88 +/- 0.54 ml/h) which was blocked by previous injection of hexamethonium but not of a tropine. These results suggest that the cholinergic system of the AMG plays a role in the control of water and salt intake.
Keywords: AMYGDALA; THIRST; SODIUM APPETITE; CHOLINERGIC STIMULATION